Microbiome and bile acid profiles in duodenal aspirates from patients with liver cirrhosis: The Microbiome, Microbial Markers and Liver Disease Study. Issue 13 (30th July 2018) - Jacobs, Jonathan P.; Dong, Tien S.; Agopian, Vatche; Lagishetty, Venu; Sundaram, Vinay; Noureddin, Mazen; Ayoub, Walid S.; Durazo, Francisco; Benhammou, Jihane; Enayati, Pedram; Elashoff, David; Goodman, Marc T.; et al.
Abstract : Aim: Cirrhosis is a leading cause of death worldwide, yet there are no well‐established risk stratifying tools for lethal complications, including hepatocellular carcinoma (HCC). Patients with liver cirrhosis undergo routine endoscopic surveillance, providing ready access to duodenal aspirate samples that could be a source for identifying novel biomarkers. The aim of this study was to characterize the microbiome and bile acid profiles in duodenal aspirates from patients with liver cirrhosis to assess the feasibility of developing biomarkers for HCC risk stratification. Methods: Thirty patients with liver cirrhosis were enrolled in the Microbiome, Microbial Markers, and Liver Disease study between May 2015 and March 2017. Detailed clinical and epidemiological data were collected at baseline and at 6‐monthly follow‐up visits. Duodenal aspirate fluid was collected at baseline for microbial characterization using 16S ribosomal RNA sequencing and bile acid quantification using mass spectroscopy. Results: Alcohol‐related cirrhosis was associated with reductions in the Bacteroidetes phylum, particularly Prevotella (13‐fold reduction), and expansion of Staphylococcus (13‐fold increase), compared to hepatitis C virus‐related cirrhosis. Participants with hepatic encephalopathy (HE) had less microbial diversity compared to patients without HE ( P  < 0.05), and were characterized by expansion of Mycobacterium (45‐fold increase) and Gram‐positive cocci including Granulicatella (3.1‐fold increase), unclassified Planococcaceae (3.3‐fold increase), and unclassified Streptococcaceae (4.5‐fold increase). Non‐Hispanic White patients had reduced microbial richness ( P  < 0.01) and diversity ( P  < 0.05), and increased levels of conjugated ursodeoxycholic acid (glycoursodeoxycholic acid and tauroursodeoxycholic acid, P  < 0.05) compared to Hispanic patients. Conclusion: Microbial profiles of duodenal aspirates differed by cirrhosis etiology, HE, and Hispanic ethnicity.